An exploratory study of exhibitionism amongst adult men in Perth: a qualitative perspective as a guide for treatment - Maule, Linda J. (Curtin University, 2000)
The aim of this research is to talk to a sample of exhibitionists who are currently under the supervision of the Ministry of Justice (MOJ) in Perth, Western Australia in order to ascertain whether current treatment approaches used within the MOJ are the most effective and appropriate for this group of sex offenders. It was considered that the most effective research method would be a qualitative approach in order to gain insight into the offender's understanding of their offending behaviour and to attempt to identify their areas of treatment need. Through personal observations in working with exhibitionists and supported by the literature, an interview schedule was developed to combine a detailed social history with questions on communication, childhood issues, father issues and stress. Twenty voluntary participants were interviewed, having been accessed through the correctional community and prison environments. The objectives were (1) To identify any categories of exhibitionists and therefore better utilise treatment resources, (2) To identify the role of stress and communication deficits in offending behaviour of exhibitionists, (3) To determine whether exhibitionists would be more effectively treated within their own discrete population or with other types of sex offenders and (4) To identify a more appropriate treatment model. Another area of interest which was not specifically focussed on was whether findings would emerge which could predict which exhibitionists would progress to more serious sexual offending.The study found 3 categories of exhibitionist (1) Adolescent Onset Career Exhibitionists, (2) Adult Onset Career Exhibitionists and (3) Situational Response Exhibitionists. Whilst the first 2 categories contained participants whose offending was entrenched once commenced, either in early adolescence or adulthood, the latter group appeared to offend as a specific response to a life crisis. Further, findings indicated that there were 3 levels of communication deficits ranging from poor communication (65% of participants) to an inability to express negatively perceived emotions such as sadness or fear. All but one participant experienced high levels of stress and had difficulty coping with their symptoms. Again, all but one participant expressed unsatisfactory relationships with their fathers ranging from abandonment to emotional distance and 50% of the participants experienced physical, sexual and/or emotional abuse.A model of treatment was recommended which allowed for increased flexibility, allowing resources to be focussed on those offenders with the highest need. Further recommendations included increased liaison with the courts and Community Corrections in order to facilitate a more integrated approach to the client. It was also considered that exhibitionists should continue working within groups which contained other types of sex offenders.